DISTRIBUTION AND ABUNDANCE OF MACROINVERTEBRATES WITHIN TWO PONDS OF LNMU CAMPUS, DARBHANGA, BIHAR - SHACHI, KUMARI; KUMAR, SANJEEV; PRASAD, NAYAN KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Macroinvertebrates serve several important functions within the aquatic environment: They provide a valuable "cleaning" service by scavenging dead or decaying bacteria, plants, and animals, which helps recycle nutrients back into the system. They are an important food for fish, birds, amphibians and reptiles. The sample of macroinvertebrates were taken at three points characterized by different kinds of vegetation of both the investigating sites i.e. Anandbag Pond (P1) and Manokamana Temple pond (P2). Microbenthic sample for selections were collected monthly during study period. The Collected sample were washed and microbenthic invertebrates were transferred to vials containing 5% formalin for further identification. The organisms were segregated and their abundance was calculated as no. per square meter. Preserved sample of macro benthic invertebrates were identified.The qualitatively microbenthic invertebrates analysis showed the presence of three species of phylum Annelida belonging to class Hirudinea (Poecilobdella granulosa, Savigny 1822) and Oligochaete (Pheretima posthuma), six species of phylum Arthropoda belonging to three orders, Decapoda (Palaemon malcolmsonii), Diptera (Chironomus sp.,Culicoides sp., Tabanus sp.) and Colepteran (Berosus sp. Hydroglyphus sp.) and only one species of Mollusca belonging to family Ampullariidae (Pila globosa).During the course of study, 9 taxa were collected from the study area, of these, phylum Arthropoda contributed the largest share constituting 56.9% in p1 pond and 56.2% in P2 pond during 2012 and 56.7% and 55.6% in P1 and P2 pond respectively during 2013 and 27.7% in P1 pond and 27.8% in P2 pond of the total macroinvertebrates respectively. Phylum Mollusca was found in very less amount, it is contributed to share 14.9% in P1 pond and 16.0% in P2 pond during 2012 and 15.06% in P1 pond and 16.9% in P2 pond during 2013, of the total macroinvertebrates respectively. For statistical analysis, the microbenthic invertebrate fauna were analyzed species diversity, species richness, dominance and evenness which showed great variations. Manokamana Temple pond was more rich macroinvertbrates in comparison to Anandbag pond. The total no. of macroinvertebrates in P1 pond was 1154 and P2 was 1188 (year2012) and p1 was 1188, P2 pond was 1195 (2013). In Year 2012, phylum Annelida was varied from 8 to 50 in P1 pond and 7 to 52 in P2 pond, phylum Arthropods was varied from 30 to 78 in p1 pond and 32 to 75 in P2 pond while phylum Mollusca was varied from 4 to 32 in P1 pond and 6 to 34 in p2 pond. During 2012 the total number of Annelida, Arthropods and Mollusca was 324, 657 and 173 in P1 pond and 328, 664 and 189 in P2 pond found respectively. Similarly in year 2013, phylum Annelida was varied from 8 to 50 in P1 pond and 9 to 35 in P2 pond, phylum Arthropoda was varied from 32 to 79 in P1 pond and 7 to 35 in P2 pond respectively. During 2013 the total no. of Annelida, Arthropods and Mollusca was 329, 674 185 in P1 pond while 329, 664 and 202 pond recorded respectively. The contribution of arthropods were highest in both representative ponds and least number of molluscans in both ponds during (year 2012 and 2013) course of study. The application of diversity indices has revealed considerably high diversity of P2 pond fauna than p1 pond fauna. Very little differences were found between the both ponds with reference to macroinvertebrates. Moreover, our study confirms the role of distribution and abundance of Macro-invertebrates and in maintaining high biodiversity and suggests that both ponds should be considered to provide both an exhaustive collection of species for pond management and conservation and basic insights into the functioning of pond communities.